Dual port vapor injected compression: In-system testing versus test stand testing, and mapping of results. (March 2016) - Bach, Christian K.; Groll, Eckhard A.; Braun, James E.; Horton, W. Travis
Abstract: This paper introduces the differences of in-system testing of a dual-port vapor injected compressor as compared to test stand testing and presents the performance results. Single-port vapor injected compression has been studied previously, typically using scroll compressors. Single-port vapor injection employs one port with a single intermediate injection pressure, while dual-port vapor injection uses two ports at different angular locations, leading to two intermediate pressure levels for the injected vapor. The main differences between in-system testing and test stand testing can be found in suction and injection superheat values, discharge temperature, and range of injection flow rates. Dimensionless PI-type mappings are introduced that can be used for system simulation. Highlights: Dimensionless mappings for a dual-port vapor injected compressor are introduced. The mappings include mass flowrates, as well as isentropic & volumetric efficiency. Discharge temperature is mapped to allow prediction of the operating envelope. Different data sources and their effect on the mapping approach are investigated. Differences between non-vapor injection and vapor injection are shown.